2008
DOI: 10.1007/s10495-008-0234-5
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Fas/Fas ligand interaction suppresses hepatocyte apoptosis in ischemia-reperfusion rat liver

Abstract: Hepatic ischemia-reperfusion injury remains a significant problem for liver surgery, including transplantation, and apoptosis has been implicated in this type of hepatic injury. Here we found that through the Fas/Fas ligand interaction apoptosis is involved in the late phase of hepatic ischemia-reperfusion injury. The appearance of apoptotic hepatocytes increases significantly after reperfusion, reaching a maximum 12 h after reperfusion. The transcription levels of Fas and Fas ligand are increased after reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 52 publications
1
27
0
1
Order By: Relevance
“…Accordingly, the allo-FK group showed a greater Bcl-2 expression in the pericaval hepatocytes than in the syn group on day 1 after OLT. As a result, FK was thus suggested to ameliorate the I/R injury after OLT via mediating the Bcl-2 expression on hapatocytes in zone Fas action (51,52). 2) Overexpression of Bcl-2 by gene transfer (47).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the allo-FK group showed a greater Bcl-2 expression in the pericaval hepatocytes than in the syn group on day 1 after OLT. As a result, FK was thus suggested to ameliorate the I/R injury after OLT via mediating the Bcl-2 expression on hapatocytes in zone Fas action (51,52). 2) Overexpression of Bcl-2 by gene transfer (47).…”
Section: Discussionmentioning
confidence: 99%
“…22 It was reported that blockade of the Fas/FasL interaction attenuated IRI both in the kidney 23 and in the liver. 24 So we isolated thymocytes, liver mononuclear cells (MNCs) and splenocytes, which were subjected to flow cytometry analyses. The results are summarized in Table 1, and a typical result is shown in Figure 1.…”
Section: Hif-2a Knockout Led To Upregulated Fasl Expression On Periphmentioning
confidence: 99%
“…However, apoptotic cell death of hepatocytes in EBOVinfected mice has not been reported. H&E and TUNEL staining in the liver have been used to study hepatocyte apoptosis in other models (26,27). We analyzed the livers of EBOV-infected mice to determine whether hepatocyte apoptosis was present.…”
Section: Indication Of Ebov-induced Hepatocyte Apoptosismentioning
confidence: 99%